ANTIOXIDANT ACTIVITY AND ANTIKANKER DERIVATING BENZALASETON - Sri Handayani; Retno Arianingrum; Winarto Haryadi (Jurnal Penelitian Saintek, 2013)
Modification of vanillin structure to vanililacetone and divanililaseton and its activity test as antioxidant and anticancer have been done. The structural modification is carried out by condensation of the crosslinked aldol in an alkaline atmosphere with the aqueous ethanol solvent for 3 hours at 10 ° C. The antioxidant activity test on the synthesis compound was done by deoxyribose degradation method, while the anticancer activity test was done by MTT method. The results of antioxidant activity test show that the divanililaseton with IC50 is 873 ug / ml. more active than vanililacetone with IC50 of 11,765 ug / ml .. IC50 data for anticancer activity against cancer cell HeLa vanilinaseton and divanilinaseton respectively of 51.68 and 10.26 ug / ml. These results show that both compounds are very toxic to HeLa cancer cells.